2012
DOI: 10.1037/a0024955
|View full text |Cite
|
Sign up to set email alerts
|

Polarity correspondence in metaphor congruency effects: Structural overlap predicts categorization times for bipolar concepts presented in vertical space.

Abstract: Previous research has shown that words presented on metaphor congruent locations (e.g., positive words UP on the screen and negative words DOWN on the screen) are categorized faster than words presented on metaphor incongruent stimuli (e.g., positive words DOWN and negative words UP). These findings have been explained in terms of an interference effect:The meaning associated with UP and DOWN vertical space can automatically interfere with the categorization of words with a metaphorically incongruent meaning. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(156 citation statements)
references
References 61 publications
9
145
1
1
Order By: Relevance
“…In addition, our results are conceptually in line with theoretical frameworks that stress the importance of opposition and alignment along dimensions (Becker, 1980;Lakens, 2012;Lakens et al, 2012;Paradis & Willners, 2011;Scherer & Lambert, 2009;P. Walker, 2016;L.…”
Section: Predicting Context-dependent Associationssupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, our results are conceptually in line with theoretical frameworks that stress the importance of opposition and alignment along dimensions (Becker, 1980;Lakens, 2012;Lakens et al, 2012;Paradis & Willners, 2011;Scherer & Lambert, 2009;P. Walker, 2016;L.…”
Section: Predicting Context-dependent Associationssupporting
confidence: 76%
“…How does the context activate specific dimensions of meaning? Based on literature on this topic, we assume that polar oppositions activate the dimension they are opposed on (Becker, 1980;Lakens, 2012;Lakens, Semin, & Foroni, 2012;Paradis & Willners, 2011;Scherer & Lambert, 2009;Willners & Paradis, 2010). For example, studies of antonymy in the field of linguistics suggest that concept pairs in an antonym relationship (e.g., good vs bad) evoke properties of the same underlying dimension (e.g., goodness; Paradis & Willners, 2011;Paradis, van de Weijer, Willners, & Lindgren, 2012).…”
Section: Dimension Specificity Hypothesismentioning
confidence: 99%
“…Based on the ' danger' versus 'safe' association (Pravossoudovitch et al, 2014), we expected that red would form the minus pole on the evaluation dimension, whereas green would form the plus pole on the evaluation dimension. Similarly, research has shown that positive forms the plus pole on the evaluation dimension, whereas negative forms the minus pole on the evaluation dimension (e.g., Lakens, 2012;Osgood & Richards, 1973). Based on these polarity attributions, we expect associations to emerge between red and negative, and green and positive.…”
Section: Sample Size Justification and Statistical Analysesmentioning
confidence: 99%
“…We manipulated the color opposition (i.e., either red vs blue or red vs green stimulus figure categorizations) and the word pairs (i.e., positive vs negative, aggressive vs calm, and enthusiastic vs relaxed attribute categorizations) across a set of five implicit association tests (IAT, Greenwald, McGhee, & Schwartz, 1998). Based on earlier studies that have examined how polar opposites activate conceptual dimensions (e.g., Lakens, 2012;Lakens, Semin, & Foroni, 2012;Paradis & Willners, 2011), we expected that red in opposition to green would activate the evaluation dimension based on its association with ' dangerous' versus 'safe', whereas red in opposition to blue would activate the activity dimension based on its association with 'hot' vs ' cold' (Osgood et al, 1957). We relied on these context-dependent associations to test a prediction from the dimensionspecificity hypothesis that red as opposed to blue would be associated with highly active (negative) concepts such as aggression (Experiment 4), but also with highly active (positive) concepts such as enthusiasm (Experiment 5).…”
Section: Current Experimentsmentioning
confidence: 99%
“…Reviews of the social embodiment literature often summarize a wide range of research areas such as facial feedback (e.g., Strack, Martin, & Stepper, 1988), cross-modal stimulus response congruency effects (e.g., Meier & Robinson, 2004;Schubert, 2005;Lakens, 2012), and approach avoidance effects (e.g., Rotteveel & Phaf, 2004;Eder & Rothermund, 2008). When we turn to research that examines whether sensorimotor information influences social inferences, there are some reasons to worry about the robustness of the empirical knowledge base.…”
Section: A Critical Look At the Empirical Datamentioning
confidence: 99%